The Influence Of Authoritarian Leadership Style On The Performance Of Officials At The Pajalesang Village Office - Umar Umar; Eva Selviana; Nelli Viranda (GENTARA: management and accounting research, 2026)
This study aims to determine the influence of authoritarian leadership style on the performance of officials at the Pajalesang Village Office, Lilirilau District, Soppeng Regency. Based on the results of preliminary field observations, it was found that the implementation of tasks at the Pajalesang Village Office still faces several obstacles, such as low coordination between leaders and subordinates, frequent delays in activity reporting, and one-way communication from the leader. An authoritarian leadership style is characterized by centralized decision-making, one-way communication, and strict supervision of officials. This study uses a quantitative approach with an associative research design. The population in this study consists of all 9 officials of the Pajalesang Village Office, who were also used as the sample through a total sampling technique. Data were collected through observation, interviews, and questionnaires, and then analyzed using simple linear regression analysis and the t-test. The results show that the authoritarian leadership style has a positive and significant effect on the performance of village officials, as evidenced by a regression coefficient value of 0.612 and a significance value of 0.006 < 0.05. This indicates that the implementation of a firm and structured authoritarian leadership style can improve discipline, work effectiveness, and the achievement of officials’ performance in a village office environment with a limited number of staff. However, the application of an authoritarian leadership style needs to be balanced with good communication in order to avoid reducing officials’ motivation and creativity